Magnetic Resonance Imaging Biomarkers of Bone and Soft Tissue Tumors - Ghasemi, Ali; Ahlawat, Shivani; Fayad, Laura Marie (Seminars in Musculoskeletal Radiology, 2024)
Magnetic resonance imaging (MRI) is essential in the management of musculoskeletal (MSK) tumors. This review delves into the diverse MRI modalities, focusing on anatomical, functional, and metabolic sequences that provide essential biomarkers for tumor detection, characterization, disease extent determination, and assessment of treatment response. MRI's multimodal capabilities offer a range of biomarkers that enhance MSK tumor evaluation, aiding in better patient management.
Keywords: magnetic resonance imaging; biomarker; sarcoma; bone tumor; soft tissue tumor